(untitled) (Research, Society and Development, 2022)
Most cases of dental trauma occur during childhood, mainly due to falls and accidents at school or at home. The region of the mouth most affected by trauma is the maxilla, the mandible is less affected. A traumatic tooth injury causes damage to many dental structures and adjacent tissues and the possibility of successful endodontic treatment is very high when performed correctly. The patient in this report suffered trauma when he was 11 years old and, more than a decade later, with the darkening of tooth 11, he sought dental treatment and discovered extensive periapical lesions involving teeth 11, 12, 21 and 22. Teeth 11 and 12 passed by endodontic surgery and teeth 21 and 22 had non-surgical treatment. This article aims to compare the cicatrization of traumatized teeth with extensive periapical lesions that underwent conventional endodontic treatment with and without surgical complementation, and also to highlighting the use of bioceramic materials. It was concluded that endodontic treatments with and without surgical complementation were effective, each one suitable for the individual conditions of each tooth.